Spatial Analysis of Environmental Factors in the Dengue Hemorrhagic Fever Incident at Soe City District - Bakung, Paulus Innocentius; Landi, Soleman; Sir, Amelya B (Journal of Public Health for Tropical and Coastal Region, 2024)
Introduction: In 2022, there was a large increase in cases resulting in extraordinary events cases in the TTS district with the number 226 cases. Half of the percentage of outbreak cases that occurred in Soe City with a number of cases is 134 cases. Spatial analysis can be used to see patterns of disease distribution in certain areas.Methods: This research is a type of descriptive research with a case study approach. This descriptive research was carried out using a survey method where there was no intervention on variables but simply observing natural phenomena or looking for relationships between these phenomena and other variables.Results:  The research of dengue case data is divided into univariate analysis and spatial analysis, for example, classification, buffering and Moran index. Environmental factors in the form of the existence and condition of water reservoirs with dengue fever incidents can be seen in data related to the number of water reservoirs used by the community which are left open and the number is >3, making it easier for mosquitoes to breed. In the Spatial Classification Analysis, Nonohonis Village has the highest level of risk, but Autocorrelation Analysis states that the Oekefan area has larger cluster points than Nonohonis Village. Furthermore, environmental factors include the existence and condition of dug wells. at a depth of ≤15m with open conditions makes it easier for mosquitoes to breed. Apart from that, based on the buffer data above, it can be seen that at a radius of <100m it is 3 times larger than a radius of 100 to 300m and 2.7 times larger than a radius of 300m to 500m. Environmental factors include the existence and condition of waste water drainage channels (SPAL) with dengue fever incidents. Based on the buffer data above, it can be seen that at a radius of <100m it is 0.6 times greater than the radius from 100 to 300m and 0.8 times greater than the radius from 300m to 500m.Conclusion: It is necessary to control mosquito breeding in water reservoirs and dug wells through education regarding malaria risk factors in Soe City.